LC-MS-MS quantitative analysis reveals the association between FTO and DNA methylation - Zhu, Yuting; Zhou, Guangyu; Yu, Xuebin; Xu, Qiang; Wang, Kai; Xie, Dan; Yang, Qingkai; Wang, Lina (PLOS ONE, 2017)
Fat mass and obesity-associated protein (FTO) is α-ketoglutarate-dependent dioxygenase and responsible for demethylating N6-methyladenosine (m6A) in mRNA, 3-methylthymine (m3T) in single-stranded DNA (ssDNA) and 3-methyluracil (m3U) in single-stranded RNA (ssRNA). Its other function remains unknown but thousands of mammalian DNA show 5-methyl-2'-deoxycytidine (5mdC) modification and 5mdC demethylases are required for mammalian energy homeostasis and fertility. Here, we aimed to confirm whether FTO proteins can demethylate 5mdC in DNA. However, we found that FTO exhibits no potent demethylation activity against 5mdC in vitro and in vivo by using liquid chromatography-tandem mass spectrometry (LC-MS-MS). The result showed FTO demethylase has the characteristics of high substrates specificity and selectivity. In addition, we also used immunofluorescence technique to demonstrate overexpression of wild type TET2, but not FTO and mutant TET2 in Hela cells results in higher levels of 5-hydroxymethyl-2'-deoxycytidine (5hmdC) generated from 5mdC. In conclusion, our results not only reveal the enzymatic activity of FTO, but also may facilitate the future discovery of proteins involved in epigenetic modification function.